Thirty‐five years of the Journal of Computer Assisted Learning: A bibliometric overview. (Journal of Computer Assisted Learning, 2022)
Background: Journal of Computer Assisted Learning (JCAL), which started its publication life in 1985, is a leading international journal in the field of computer and instructional technologies and celebrated its 35th anniversary in 2020. Objectives: This study aims to provide a bibliometric overview of leading publication and citation trends of JCAL over the past 35 years. In order to achive the aim of the study, metadata of all the articles (N = 1305) published in the journal in this process were obtained from the Scopus database. Methods: The study includes JCALs bibliometric analyses such as the total number of articles and citations, h‐index, citations per paper, citations per year, citation thresholds, average number of citations per year and annual citation counts between 1985 and 2020. In addition, the study presents visual maps based on citation, co‐citation, bibliographic coupling, co‐authorship and co‐occurrence of author keywords with a bibliometric mapping analysis performed with VOSviewer software. Results and Conclusions: The results indicate that JCAL has become one of the leading journals over time in the field of computer and instructional technologies, as indicated by citation counts of articles published in JCAL, receiving citations from publications in esteemed journals, and publishing international rigorous work. Additionally, researchers who have published in JCAL in recent years have directed their attention to subjects such as learning analytics, massive open online courses (MOOCs), multimedia learning, game‐based learning, blended learning, online learning, mobile learning and virtual reality. Implications: Further investigation of the scientific collaboration of authors who conduct research in different disciplines related to education, topics and education levels may yield more diverse perspectives. Lay Description: What is already known about this topic?: The rapid increase in interest in educational technologies creates the expectation that high quality articles in this field will be systematically reviewed.With the constant growth of scientific literature data in recent years, there has arisen a need to work with large scale data sets called big data. What this paper adds?: The knowledge generation patterns in the content of journal were reviewed through a general bibliometric look at the leading publication and citation trends that have occurred in JCAL during the past 35 years.In order to investigate JCAL bibliometrically, to main perspectives, namely productivity and influence, were taken into consideration.The bibliometric meta data of JCAL were graphically mapped using VOSviewer software. Implications for practice and/or policy: The nature of the publications and citations during the 35‐year life span of JCAL has been revealed.The leading authors, institutions and countries in the 35‐year life span of JCAL have been determined.The 35‐year life span of JCAL has been graphically mapped using VOSviewer software.The results indicate that JCAL has made significant progress from past to present.